Comparison of efficacy of lateral sphincterotomy versus topical 0.2% Glyceryl Trinitrate Ointment in anal fissure treatment - Ghaffar, Naeem; Majeed Ch, Salman; Majeed Ch, Wasif; Ghufran, Samar; Hussain, Shahid; Jamil, Amreem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcomes of both 0.2% glyceryl trinitrate and lateral sphincterotomy to treat the anal fissure. Study design: Comparative study. Methods: This study was performed at the surgery department sir Ganga Ram Hospital hospital Lahore, Pakistan from 1st June 2020 to 30 Dec 2021. Total 80 patients were the participant of this study. After the diagnosis of anal fissure and before the starting treatment, a detailed scenario of its treatment, process, side effects, and chances of recurrence were explained to patients then consent was signed by the individual patients. Patients were divided into two groups to compare the outcomes of both sphincterotomy and glyceryl trinitrate. Group A had 40 patients and Group B had 40 patients as well. The age of all the patients was above the 18 years. Results: Group A had 14 (35%) patients of age range 18-30 years and 26 (65%) of 31-60 years old. 13 (32.5%) females, 27 (67.5%) males, mild pain in 10 (25%), severe pain in 30(75%), Constipation was reported in 16(40%) patients and 29(72%) patients had bleeding issues. Group B found with 17 (42.5%) patients of age range 18-30 years and 23 (57.5%) of 31-60 years old. 10 (25%) females, 30 (75%) males, mild pain in 12 (30%), severe pain in28(70%), Constipation was reported in 20(50%) patients and 31(77%) patients had a bleeding issue. The final comparison after six weeks of treatment shows the 65% of patients healed with the lateral sphincterotomy and 47% of patients healed with ointment of 0.2% glyceryl trinitrate. The healed proportion was measured high for the lateral sphincterotomy treatment as compared to the ointment of 0.2% glyceryl trinitrate. Conclusion: We concluded that lateral sphincterotomy has an effective response to treat the anal fissure as compare to 0.2% ointment of glyceryl trinitrate.